Comparison of EMG activity during stable and unstable push-up protocols - Anderson, G. S.; Gaetz, M.; Holzmann, M.; Twist, P. (European Journal of Sport Science, 2013)
This experiment examined muscle activation measured using electromyography (EMG) during a standardized push-up performed on stable and unstable surfaces. Fifteen highly trained participants performed four push-ups: standard (hands and feet on the floor), either the hands or feet on an unstable surface (single instability), and with both hands and feet on unstable surfaces (dual instability). Unstable surfaces were created using a stability ball and an extreme balance board. EMG activity was recorded from three core stabilizers (erector spinae, rectus abdominus and internal obliques), one prime mover (triceps), and one lower body stabilizer (soleus). The EMG time series were smoothed using a 10-point moving average and root mean squares (RMS) were calculated for the entire time series. The results showed that push-ups performed with dual instability had significantly greater EMG activation compared to single instability or the stable push-up. In addition, as instability increased, there was a greater amount of muscle activation for the core stabilizers, prime movers and lower body stabilizers. The findings are consistent with the position that unstable surfaces in conjunction with standard exercises can be used to increase activation of core trunk stabilizers. This may in turn provide increased trunk strength and greater resistance to injury.